SYNTHESIS OF NEW ACTIVATED INDOLES; 3-(4’-BROMOPHENYL)-4,6-DIMETHOXY-2-METHYLINDOLE - Tutik Dwi Wahyuningsih (Indonesian Journal of Chemistry, 2004)
3-(4'-Bromophenyl)-4,6-dimethoxy-2-methylindole has been synthesized from 4,6-dimethoxyaniline via the modified Bischler method. Reaction of 4,6-dimethoxyaniline with 2,4-dibromopropiophenone gave an aniline ketone in 85%, and then it was protected to give the amido ketone as a white solid. Cyclization of amido ketone was performed by trifluoroacetic acid and subsequent deprotection with potassium hydroxide in methanol afforded a white solid of 3-(4'-bromophenyl)-4,6-dimethoxy-2-methylindole in 86%.